Implementasi Video Conference dengan File Sharing menggunakan WebRTC - Fathi Nur Azzam; Dany Primanita Kartikasari; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Meeting or consultation serves to bring two or more people to discuss together. Technology serves to facilitate access communication meetings and consultations are video conferencing. Video conferencing is communication using audio and video which connects users even though they are not in the same place and time. There is a service to share data or called file sharing when using video conferencing. Applications support video conferencing and file sharing is Skype, Cisco Webex, and Zoom. However, the above application has a disadvantage that each operating system is different and application installation is required for each different device. WebRTC is a solution to the problem. WebRTC can run on all browsers, open-source, and free. WebRTC uses JavaScript-based APIs to establish peer-to-peer connections. WebRTC requires two additional servers namely STUN and TURN to communicate peer-to-peer through NAT. Testing is to measure the reliability of file sharing to video conferencing. Testing is using six types of connections and three types of file sizes. First test result file sharing does not affect video conferencing because it runs on a different port. One Way Delay test results increase in line with the increase in the size of the file sent.